PENGARUH EMPLOYEE ENGAGEMENT DAN PERCEIVED ORGANIZATION SUPPORT TERHADAP KINERJA KARYAWAN - Rival Muttakin; Khairul Bahrun (Yayasan Insani Mandiri Santani, 2026)
This study aims to determine the effect of Employee Engagement and Perceived Organization Support on the performance of employees of the Public Works and Spatial Planning Agency (Pupr) of Kepahiang Regency. This research is a quantitative descriptive study, with the population being employees of the Public Works and Spatial Planning Agency (Pupr) of Kepahiang Regency as the research subjects. The data collection techniques used were observation, interviews, and questionnaires. Meanwhile, the analysis technique used descriptive analysis and multiple linear regression analysis with hypothesis testing. The results of this study show that employee engagement has a positive effect on the performance of employees of the Public Works and Spatial Planning Agency (Pupr) of Kepahiang Regency. This means that the higher the level of employee engagement, the higher the level of employee performance. Perceived Organization Support has a positive effect on the performance of employees of the Public Works and Spatial Planning Agency (Pupr) of Kepahiang Regency. The better the level of Perceived Organization Support, the higher the level of employee performance. Employee engagement and Perceived Organization Support simultaneously or together have a positive and significant effect on the performance of employees of the Public Works and Spatial Planning Agency (Pupr) of Kepahiang Regency. This means that if the level of Employee Engagement and Perceived Organization Support in the Public Works and Spatial Planning Agency is high, it will improve the performance of employees of the Public Works and Spatial Planning Agency (PUPR) of Kepahiang Regency. Keywords: Employee Engagement, Perceived Organization Support, Employee Performance